ESENSI BENTUK TOPENG PADA LUKISAN DYAN ANGGRAINI DALAM PERSPEKTIF SEMIOTIKA - Fasmaqullah Fasmaqullah (Universitas Sarjanawiyata Tamansiswa, 2020)
The aim of this research was to find out the essence of mask shape of Dyan Anggraini’s painting in semiotics perspective.This research was descriptive research and the main instrument was the researcher. The subject of the research was the mask of Dyan Anggraini’s painting. Then, the object of the research was the essence of mask shape of Dyan Anggraini’s painting in semiotics perspective in a form of material object (shape, color, property, situation). The research focused on the problem related with the essence of mask of Dyan Anggraini’s painting in semiotics perspective. Data was collected through observation, interview and documentary. The data was analyzed by using descriptive qualitative technique. The validity of data was obtained through the interaction between the researcher and the resource expert.The result of the research shows: the essence of mask shape of Dyan Anggraini’s painting based on perspective theory by Charles Sander Pierce like icon, index and symbol. The icon shows about the expression of the mask, facial expression and nonverbal expression. The index of the painting contains about the culture and the Indonesian mask figure. The symbol shows the essence of mask, mask identity, which is shown through icon and index based on color, shape, property and situation. The researcher can explain that the essence of mask of Dyan Anggraini’s painting through semiotics perspective in order to make easier for the reader to understand.